Distributed algorithm for painting by a swarm of randomly deployed robots under limited visibility model. (15th October 2018) - Das, Deepanwita; Mukhopadhyaya, Srabani
This article studies the problem of painting an obstacle free rectangular region by a swarm of mobile robots. Initially the robots are deployed randomly within the target area subject to the condition that the distribution is d *-dense, whered * = 3 d 2, and a robot can view up to a distance d . By d *-dense, it is meant that if all the robots are projected on a horizontal line, then the distance between two consecutive robots must be less than or equal to d *. Non-consideration of the popular CORDA (computational) model in the field of area coverage by swarm robots has been addressed here. The proposed algorithm assumes CORDA model. The robots follow a completely distributed algorithm to paint the region. The robots do not need to be synchronous, but they are assumed to have equal velocities. However, the proposed algorithm supports the robots with different speed. In that case, if r is the given upper bound on the ratios of the speeds of any two robots, then the initial distribution has to be D *-dense, whereD * = d 4 ( 3 − r ) ( r + 5 ) 1 ≤ r < 3 .